(untitled) (Estudos em Design, 2021)
Programmable toys seek to help children in their first contacts with algorithms and facilitate the development of Computational Thinking. This article examines programmable toy interfaces and describes the design process for three programming interfaces for RoPE (Educational Programmable Robot). The first interface targets children aged from 3 to 6 years old and have colorful physical buttons. The second interface is a smartphone app that allows programming by fitting blocks and keeps the sync with the physical buttons of the toy. Finally, the third is a tangible block interface, designed to allow natural interaction and collaboration. A quantitative evaluation of the application showed that the use of physical buttons is more efficient than dragging blocks on a smartphone screen. We evaluated qualitatively the tangible interface through video and content analysis. The analysis shows that children often read the tangible blocks, which encouraged the debugging of an algorithm and collaboration between students.